2019
DOI: 10.1039/c8sc05362f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of magnetisation relaxation in {MIII2DyIII2} (M = Cr, Mn, Fe, Al) “Butterfly” complexes: how important are the transition metal ions here?

Abstract: Tuning of relaxation of magnetisation through 3d metal ion variations in 3d2Dy2 butterflies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Indeed, it has been shown that the incorporation of these cations can influence the electron density distribution of surrounding coordinating ligands, thus affecting the electronic structure and the magnetization relaxation properties of the Ln(III) ions. [18,19] We and others have been exploring this type of systems with Co(III) as the diamagnetic metallic site. Among all reported structurally characterized compounds adjusting to the {Co III 2 Ln III 2 } content approximately 40 entries are found in the CCDC database up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been shown that the incorporation of these cations can influence the electron density distribution of surrounding coordinating ligands, thus affecting the electronic structure and the magnetization relaxation properties of the Ln(III) ions. [18,19] We and others have been exploring this type of systems with Co(III) as the diamagnetic metallic site. Among all reported structurally characterized compounds adjusting to the {Co III 2 Ln III 2 } content approximately 40 entries are found in the CCDC database up to now.…”
Section: Introductionmentioning
confidence: 99%
“…15 This methodology has been established as a reliable tool to predict g-tensors and energies of low lying states for 4f, 3d-4f, and 4f-4f complexes. 11,19,20,30,[33][34][35][36][37][38][39][40] We have computed eight low lying Kramer's Doublets (KDs) corresponding to 6 H 15/2 state. For all these complexes, the eight low-lying KDs lie within an energy span of 717 -1092 cm -1 (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The compounds are essentially isostructural to the [Fe III 2 Dy III 2 (μ 3 -OH) 2 (teaH) 2 (p-Me-PhCO 2 ) 6 ] (15) compound. [20,29] As can be seen from the structure of the Dy III compound 19 shown in Figure 14a, the protonated chelating alcohol arm of the teaH 3 ligand which is attached to the Ln III centres has been replaced by a picolyl arm. The dc magnetic measurements revealed the expected dominant antiferromagnetic interactions between the magnetic centres for the {Fe III 2 Ln 2 } systems as was the case for the previously reported {Fe III 2 Ln 2 } systems.…”
Section: Teah à To Pmide àmentioning
confidence: 99%